Design Of Web-Based Coffee Sales System (Case Study: CV Cahaya Abadi) - Muhammad Choir Ridho Azizi; Yulian Findawati (Procedia of Engineering and Life Science, 2022)
In this era of interconnectedness, technological progress occurs very quickly. One technology that istrending and has been widely accepted by almost everyone around the world is e-commerce. However, in Indonesiaitself, there are still many businesses that are still done conventionally, such as CV. Cahaya Abadi. This causesbusiness processes to not work efficiently, especially during transaction processing. Another problem is the lack ofreporting tools that accurately reflect performance indicators such as total customers and total sales volume, so thatcompany performance cannot be monitored. The purpose of this research is to create an integrated web-based salessystem that is intended as an integrated sales system that has various features for users and allows Cahaya Abadi tomanage the entire business in one place in a structured manner. In this study, the waterfall method is used as adevelopment method. The result of this research is a web-based sales system that is expected to be useful for salesmedia and transaction monitoring. Based on the results, the percentage of the overall quality of the sales system is84%, so this system is feasible for mass use.